2007
DOI: 10.1590/s0103-05822007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do estado nutricional e do desenvolvimento neuropsicomotor em crianças freqüentadoras de creche

Abstract: OBJETIVO: Avaliar o estado nutricional e o desenvolvimento neuropsicomotor em crianças freqüentadoras de uma creche. MÉTODOS: Estudo transversal de 113 crianças com seis a 70 meses de idade, que freqüentavam a creche Irmã Sheila em Catanduva, São Paulo. A avaliação nutricional foi feita por antropometria e analisada pela classificação de Waterlow e a avaliação do desenvolvimento neuropsicomotor pelo Teste de Denver II, em todas as crianças incluídas no estudo. Dados adicionais foram obtidos por meio de um ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
60

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 14 publications
5
47
0
60
Order By: Relevance
“…This finding corroborates other studies conducted in public early childhood education schools [17][18][19][20] , where the percentage of language deficits was found to be around 30%. The relevant literature 21 showed that language disorders are the most frequent issues in the development of preschool-age children.…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates other studies conducted in public early childhood education schools [17][18][19][20] , where the percentage of language deficits was found to be around 30%. The relevant literature 21 showed that language disorders are the most frequent issues in the development of preschool-age children.…”
Section: Discussionsupporting
confidence: 92%
“…Approximate results were also recorded in previous studies that used the same instrument. [19][20][21] However, similar studies have found sex interference in the performance of children submitted to DDST II, demonstrating that there tends to be a correlation between the sex of the child and the variable that designates the outcome stated by evaluation of devel-opmental areas. 21 This fact can be linked to the expectations that society has today in relation to different skills/ways of being of boys and girls, as well as the fact they develop faster than they do with regard to physical maturity 27 .…”
Section: Discussionmentioning
confidence: 96%
“…21,22 It is assumed that environmental conditions in which children are being raised in other regions, such as northern Brazil, can be more damaging to child development due to social and regional inequalities which the country features historically. According to Issler and Giugliani, 12 children, because of their vulnerability, are the ones suffering the damaging effects of poverty and lack of education.…”
Section: Discussionmentioning
confidence: 99%
“…Resultado diferente foi observado em estudo desenvolvido em creches beneficentes do município de São Paulo, que demonstrou prevalência similar de desnutrição (7%) e obesidade (6%) (17) . Outra pesquisa com crianças de creche da cidade de Catanduva (18) também evidenciou maior número de obesos (16%), comparado ao número de desnutridos (11%), embora a prevalência de distúrbios nutricionais tenha sido maior que a da presente pesquisa. Corso et al (19) avaliaram crianças menores de seis anos na cidade de Florianópolis, Santa Catarina, e também demonstraram maior prevalência de sobrepeso/obesidade (6,8%) comparada à de desnutrição aguda (2%).…”
Section: Discussionunclassified